Cell Death in Escherichia coli dnaE(Ts) Mutants Incubated at a Nonpermissive Temperature Is Prevented by Mutation in the cydA Gene - Strauss, Bernard (American Society for Microbiology, 2004)
Cells of the Escherichia coli dnaE(Ts) dnaE74 and dnaE486 mutants die after 4 h of incubation at 40°C in Luria-Bertani medium. Cell death is preceded by elongation, is inhibited by chloramphenicol, tetracycline, or rifampin, and is dependent on cell density. Cells survive at 40°C when they are incubated at a high population density or at a low density in conditioned medium, but they die when the medium is supplemented with glucose and amino acids. Deletion of recA or sulA has no effect. We isolated suppressors which survived for long periods at 40°C but did not form colonies. The suppressors protected against hydroxyurea-induced killing. Sequence and complementation analysis indicated that suppression was due to mutation in the cydA gene. The DNA content of dnaE mutants increased about eightfold in 4 h at 40°C, as did the DNA content of the suppressed strains. The amount of plasmid pBR322 in a dnaE74 strain increased about fourfold, as measured on gels, and the electrophoretic pattern appeared to be normal even though the viability of the parent cells decreased 2 logs. Transformation activity also increased. 4′,6′-Diamidino-2-phenylindole staining demonstrated that there were nucleoids distributed throughout the dnaE filaments formed at 40°C, indicating that there was segregation of the newly formed DNA. We concluded that the DNA synthesized was physiologically competent, particularly since the number of viable cells of the suppressed strain increased during the first few hours of incubation. These observations support the view that E. coli senses the rate of DNA synthesis and inhibits septation when the rate of DNA synthesis falls below a critical level relative to the level of RNA and protein synthesis.